Identification of resistance sources and genomic regions regulating Septoria tritici blotch resistance in South Asian bread wheat germplasm - Manjeet Kumar; Xinyao He; Sudhir Navathe; Umesh Kamble; Madhu Patial; Pawan Kumar Singh (The Plant Genome)
Abstract The Septoria tritici blotch (STB) [Zymoseptoria tritici (Desm.)] of wheat (Triticum aestivum L.) is characterized by its polycyclic and hemibiotrophic nature. It is one of the most dangerous diseases affecting wheat production worldwide. Durable resistance is largely decided by the combined effect of several quantitative trait loci (QTLs) having a minor effect. Currently, STB is not important in South Asia. However, STB expanding and wider adaptability, changing climatic conditions, and agronomic practices can create a situation of concern. Therefore, dissection of the genetic architecture of adult‐plant resistance with genome‐wide association mapping and selection of resistant sources for adult plant STB resistance were carried out on a panel of South Asian germplasm. We discovered the 91 quantitative trait nucleotides (QTNs) associated with STB resistance; 23 QTNs were repetitive across the different years and models. Many of these QTNs could differentiate the mapping panel into resistant versus susceptible groups and were linked to candidate genes related to disease resistance functions within linkage disequilibrium blocks. The repetitive QTNs, namely, Q.CIM.stb.2DL.2, Q.CIM.stb_dh.2DL.3, Q.CIM.stb.2AL.5, and Q.CIM.stb.7BL.1, may be novel due to the absence of co‐localization of previously reported QTLs, meta‐quantitative trait loci, and STB genes. There was a perfect negative correlation between the stacking of favorable alleles and STB susceptibility, and STB resistance response was improved by ∼50% with the stacking of ≥60% favorable alleles. The genotypes, namely, CIM20, CIM56, CIM57, CIM18, CIM44, WK2395, and K1317, could be used as resistant sources in wheat breeding programs. Therefore, this study could aid in designing the breeding programs for STB resistance before the onset of the alarming situation of STB in South Asia.